Imposters : A Study of Pronominal Agreement - Collins, Chris, 1963- (Book collections on Project MUSE., 2012)
In this work, the authors study the interactions of imposters with a range of grammatical phenomena, including pronominal agreement, coordinate structures, Principle C phenomena epithets, fake indexicals, and a property of pronominal agreement they call homogeneity.